The Investigation of Phraseological Units in Modern English and Uzbek - Pazilova Nasibaxon Muhammadqosimovna; Askarova iroda (Zien Journals, 2022)
The article deals with the investigation of Phraseology and phraseological units in Modern English and Uzbek. In addition, it discusses the problems of teaching phraseological units.
Keywords: Phraseological Units; Idioms; Collocations; Grammar